Avaliação isocinética do joelho no pré-operatório de artroplastia total - Carolina Barreto Mozzini (ConScientiae Saúde, 2009)
The knee osteoarthrosis difficult the routine activities and the deambulation, due to the joint degeneration and the changes in muscle performance that the inferior limb affected presents. The aim of this study was to analyze the muscle concentric peak torque of the extensors and flexors muscle of the knee, through the computadorized dynamometry. It was compared 13 individuals with knee osteoarthrosis due to cartilage degeneration, in preoperative period of total arthroplasty in one of the knees, with 13 individuals without the disease. The results show that individuals affected by the disease presented significant decrease of peak torque of flexors and extensors of the knee indicated for total arthroplasty when compared with the contralateral limb, and also, presented significant decrease in peak torque of knee extensors at 180º/s when compared with the group without the disease. So, it was verified a decrease in muscle strength of extensors and flexors of the knee in subjects with knee osteoarthrosis in preoperative period of total arthroplasty.